Effectiveness of using information service with the collaborative learning through facebook improving self regulated learning - Silfa Hafizah Pulungan; Firman Firman; Riska Ahmad (International Conferences on Educational, Social Sciences and Technology)
Self regulated learning was very important in student self, but still found student who have symptoms of selfregulated learning was low, it was seen during class timestudents use smarthphone clandestinely.Efforts made in improving selfregulated learning was using information services using collaborative learning through facebook. This study was aimed to test effectiveness of using information services with the collaborative learning through facebook improving self regulated learning students.This research uses quantitative method. The type of research was Quasi Experiment with The Non Equivalent Control Group Design. The subjectswere students of national madrasah aliyahBarumun Tengah as an experimental group and students at national madrasah aliyahMarenu as the control group.The research result shows that the information services using collaborative learning through facebook was effective to improving self regulated learning students seen from the average posttest of experimental group 148.65 and control group 137.11.